PENGARUH STRATEGI PEMBELAJARAN AKTIF CRITICAL INCIDENT (PENGALAMAN PENTING) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN KELAS VIII SMPN 3 KOTA JAMBI - Anggraini, Ega Agustian; Maulia, Siti Tiara; Salam, M. (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research was conducted at SMP N 3 Jambi City, Jalan Kh. Hasan Anang, Olak Kemang, Danau Teluk sub-district, Jambi City, Jambi. At the time the research began with observations in October 2022. This research used quantitative research. The results of this research are that after carrying out the pretest and posttest in class, the hypothesis was tested using an independent sample t-test, from which it can be seen that the sig (2-tailed) value on the output is 0.000 - 0.05. Thus h0 is rejected and Ha is accepted. So it can be concluded that there is an influence of the use of critical incident active learning strategies on the PPKn learning outcomes of class VIII students at SMP N 3 Jambi City. Based on the results of the paired sample test above, it can be concluded that there is a significant influence between the pretest and posttest of the experimental class because the sig. (2-tailed) obtained 0.000 0.05. Then, based on the results of the paired sample test above, it can be concluded that there is no significant influence between the pretest and posttest of the control class because the sig. (2-tailed) obtained 0.147 0.05 To understand the difference between the two values, an independent t test was used posttest for the experimental class and the control